EP.TH.602Exploring decision-making of healthcare professionals in patients with benign large non-pedunculated colonic polyps (BLNPCP) virtually using combined focus group and nominal group technique. (28th October 2021) - Wheldon, L; Morgan, J; Lee, MJ; Riley, S; Brown, SR; Wyld, L
Abstract: Aim: We aimed to elicit key factors that influence healthcare professional decision-making when deciding treatment for BLNPCP. Background: Benign large non-pedunculated colonic polyps (BLNPCP) may harbour covert malignancy and opinions differ about the optimal treatment modality. There are several options available, including endoscopic mucosal resection, endoscopic submucosal resection, combined endoscopic laparoscopic surgery and surgical resection. Despite widespread availability of endoscopic resection techniques, there are high rates of surgery in the UK. Methods: Three focus groups of healthcare professionals, comprised of either consultant colorectal surgeons, nurse endoscopists and consultant gastroenterologists, were conducted virtually utilising the Nominal Group Technique. Meetings were recorded and transcribed verbatim. Themes were devolved using the framework approach for qualitative analysis. A priority-ranked list of factors influencing healthcare professional decision-making in this setting was generated. Results: Five main themes were identified as influencing decision-making: Shared decision making (patient preference, informed consent); Patient factors (co-morbidity, age, life-expectancy); Polyp factors (Location, size, morphology, risk of cancer); Healthcare professionals (skill-set, personal preference); System factors (techniques availability locally, regional referral networks). Nominal Group Technique generated 55 items across the three focus groups. Nurses and gastroentologists ranked patient factors (particularly drug history and tolerance of procedure) and shared decision making (patient preference) more highly then surgeons. Surgeons placed greater emphasis on polyp factors particularly location and the risk of submucosal invasive carcinoma. Conclusion: Decision making is complex and multifactorial. These results support the benefits of complex polyp MDTs and patient involvement in the decision-making. The complexity of decision-making may underpin wide variation in practice.